RE-IMMIGRATION OF EX-LAOTIAN REFUGEES IN INDONESIA: THE MEANING OF IDENTITY THROUGH NOSTALGIA FOR THE NEXT GENERATION - Armandaru, Rio; Kurnia, Lilawati (International Review of Humanities Studies, 2023)
In 1975, the communist revolution in Laos forced approximately 400,000 Lao citizens into exile. They had no other choice besides leaving their home country. These refugees are scattered in western countries and neighboring countries in Southeast Asia, including Indonesia. The detachment of the ex-refugees next generation to their home country (Laos) becomes a problem in determining their identity when they return to Laos. This research focuses on narrating the identity of the next generation of ex-Laotian refugees in Indonesia. The next generation of ex-Laotian refugees in Indonesia interprets their identity as Indonesians rather than Laotians. This study will provide an overview of how identity is interpreted as a structure of feeling for a space in the form of nostalgia. Considering the phenomenon of forced migration will form a sentimental sense that forms self-determination to define the next generation of ex-Laotian refugees' identity. Through Cultural Studies especially using ethnography, this research will examine how the identity of the next generation of ex-refugees is constructed through a series of nostalgia for their refugee places in Indonesia.